New isomorphous complexes of Co(II) and Zn(II) with the 5-nitroorotate ligand: Crystal and molecular structures, spectroscopic and DFT studies, magnetic properties and antimicrobial activities. (1st August 2022) - Helios, Katarzyna; Bednarchuk, Tamara J.; Wysokiński, Rafał; Duczmal, Marek; Wojciechowska, Agnieszka; Łukowiak, Anna; Kędziora, Anna; Małaszczuk, Michał; Michalska, Danuta
Graphical abstract: Crystal structures of new isomorphous Co(II) (1 ) and Zn(II) (2 ) complexes with 5-nitroorotate are stabilized by intermolecular O‒H···O and N‒H···O hydrogen bonds and also by C‒O···π and N‒O···π interactions. Complex 1 showed a weak antiferromagnetic exchange coupling transmitted by H‒bonds. Both 1 and 2 revealed the photoluminescent properties as well as antibacterial and antifungal activities. Highlights: Co(II) 1 and Zn(II) 2 complexes with 5-nitroorotate are characterized. Structures were determined by XRD, FTIR, Raman, UV-Vis-NIR and thermal studies. Intermolecular H‒bonds and C‒O··· π, N‒O··· π interactions stabilize the crystal packing. Both 1 and 2 revealed the photoluminescent properties. Complex 1 showed a weak antiferromagnetic exchange coupling transmitted by H‒bonds. Both complexes exhibit the antibacterial and antifungal activities. Abstract: Two novel isomorphous Co(II) and Zn(II) complexes of 5-nitroorotate have been synthesized and characterized by a single crystal X-ray diffraction, FT-IR, Raman and UV-Vis-NIR spectroscopy as well as thermal analysis. Both tetraaqua(5-nitroorotato)cobalt(II), [Co(5-NO2 HOr)(H2 O)4 ] (1 ) and tetraaqua(5-nitroorotato)zinc(II), [Zn(5-NO2 HOr)(H2 O)4 ] (2 ) crystallize in the orthorhombic system (space group Pca 21 ). Each metal ion is chelated by the carboxylate oxygen (O1) and the deprotonated nitrogen (N1) atoms of the 5-nitroorotate ligand. Four water molecules complete the distorted octahedral coordination sphere around the metal center with an elongated axial M‒O bonds. The pattern of hydrogen bonding in the crystals of (1 ) and (2 ) is somewhat different than that reported for similar metal-orotate complexes. Weak C‒O··· π and N‒O···π intermolecular interactions promote the crystal cohesion. Theoretical studies were performed using the DFT/B3LYP method and a detailed interpretation of the vibrational spectra has been made on the basis of the calculated potential energy distribution (PED). The electronic spectra and photoluminescent properties of (1 ), (2 ) and K(5-NO2 H2 Or) (3 ) were investigated. Temperature and field-dependent magnetic studies of (1 ) revealed the existence of a weak antiferromagnetic exchange coupling transmitted by medium-strong O‒H···O intermolecular hydrogen bonds. In addition, (1 ), (2 ) and (3 ) were studied in vitro for their activity against selected Gram-positive ( S. aureus ) and two Gram-negative ( E. coli, P. aeruginosa ) bacteria and one yeast ( C. albicans ).